Unraveling potential enzymes and their functional role in fine cocoa beans fermentation using temporal shotgun metagenomics - Lima, Carolina O. de C.; De Castro, Giovanni M.; Solar, Ricardo; Vaz, Aline B. M.; Lobo, Francisco; Pereira, Gilberto; Rodrigues, Cristine; Vandenberghe, Luciana; Martins Pinto, Luiz Roberto; da Costa, Andréa Miura; Koblitz, Maria Gabriela Bello; Benevides, Raquel Guimarães; et al. (Frontiers in Microbiology, 2022)
Cocoa beans fermentation is a spontaneous process, essential for the generation of quality starting material for fine chocolate production. The understanding of this process has been studied by the application of high-throughput sequencing technologies, which grants a better assessment of the different microbial taxa and their genes involved in this microbial succession. The present study used shotgun metagenomics to determine the enzyme-coding genes of the microbiota found in two different groups of cocoa beans varieties during the fermentation process. The statistical evaluation of the most abundant genes in each group and time studied allowed us to identify the potential metabolic pathways involved in the success of the different microorganisms. The results showed that, albeit the distinction between the initial (0 h) microbiota of each varietal group was clear, throughout fermentation (24–144 h) this difference disappeared, indicating the existence of selection pressures. Changes in the microbiota enzyme-coding genes over time pointed to the distinct ordering of fermentation at 24–48 h (T1), 72–96 h (T2), and 120–144 h (T3). At T1, the significantly more abundant enzyme-coding genes were related to threonine metabolism and those genes related to the glycolytic pathway, explained by the abundance of sugars in the medium. At T2, the genes linked to the metabolism of ceramides and hopanoids lipids were clearly dominant, which are associated with the resistance of microbial species to extreme temperatures and pH values. In T3, genes linked to trehalose metabolism, related to the response to heat stress, dominated. The results obtained in this study provided insights into the potential functionality of microbial community succession correlated to gene function, which could improve cocoa processing practices to ensure the production of more stable quality end products.